The impact of age of children on decision making over time use in couple families - Le, Anh; Miller, Paul (The Centre for Labour Market Research, Curtin Business School, Curtin University of Technology, 2012)
This paper examines the links between the time allocations of partners in couple families, and the impact of children on these links. The analyses are conducted on samples separated according to the age of the youngest child. In childless couple families the time allocations of partners have complementary relationships. In couple families with only older (than 12 years) children, the time allocations of partners appear to be independent. In contrast, in couple families with younger children the time allocated to home duties and employment-related activities by the partners are substitutes. Children therefore affect the time allocation decisions in couple families through reducing the apparent complementarity in time allocations of their parents.